2020
DOI: 10.1111/myc.13077
|View full text |Cite
|
Sign up to set email alerts
|

Superficial fungal infections in the department of dermatology, University Hospital Jena: A 7‐year retrospective study on 4556 samples from 2007 to 2013

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. Abstract Background: Superficial fungal infections are often seen in day-to-day clinical practice, and their prevalence continues to rise worldwide. Over the years, a change in the pattern of dermatophytoses has been noted. Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 30 publications
5
16
0
Order By: Relevance
“…We reported that dermatophytosis was the second common type of SFI (34.8%), which is in line with previous studies 7 . However, in epidemiologic studies in China, Turkey, and Germany, 82%, 74%, and 83.2% of dermatophytosis were reported, respectively 26,28,31 . In this study, the nails were the most affected anatomic site in the patients, as similarly reported in Egypt and Southern China 18,27 .…”
Section: Discussionsupporting
confidence: 91%
“…We reported that dermatophytosis was the second common type of SFI (34.8%), which is in line with previous studies 7 . However, in epidemiologic studies in China, Turkey, and Germany, 82%, 74%, and 83.2% of dermatophytosis were reported, respectively 26,28,31 . In this study, the nails were the most affected anatomic site in the patients, as similarly reported in Egypt and Southern China 18,27 .…”
Section: Discussionsupporting
confidence: 91%
“…The present study provides insights into the prevailing dermatophytes in Switzerland. It reveals the dominance of T. rubrum as reported in Europe since the nineties [4,5,17,18], the incidence of T. violaceum and T. soudanense causing tinea capitis in patients of African and Mediterranean origin (mostly immigrants), and the appreciable frequency of T. mentagrophytes, T. benhamiae and M. canis as zoophilic species in the young Swiss autochthonous population.…”
Section: Discussionmentioning
confidence: 72%
“…The significance of some important non-dermatophyte moulds, such as Cladosporium, Alternaria, Fusarium, Scopulariopsis, Chaetomium, Sarocladium and Bipolaris in causing skin infections, has been well documented. 37,[60][61][62][63][64][65][66][67] Moreover, in cutaneous mucormycosis, the most frequently encountered genera include Rhizopus, Mucor, Lichthemia and Apophysomyces. [68][69][70][71][72] Among the yeasts, Candida is considered to be the most common fungal pathogen affecting humans.…”
Section: Ae Ti Olog I C Al Ag Ents For Superfi Cial Mycos E Smentioning
confidence: 99%
“…35,[157][158][159][160][161][162][163][164][165] On the other hand, some of the studies conducted in Iran, Poland, Malaysia, Singapore, Canada, Melbourne and Germany reported a higher incidence of superficial mycoses in males than females. 67,[166][167][168][169][170][171] Therefore, it seems difficult to categorise the most prevalent sex group affected by superficial mycoses as prevalence may depend on a number of factors, such as hormonal regulation, environmental factors, genetic predisposition, ethnic, social and cultural background. 172…”
Section: Sexmentioning
confidence: 99%
See 1 more Smart Citation